Corrosion inhibition of mild steel by N(4)-substituted thiosemicarbazone in hydrochloric acid media - Sam John; R. Jeevana; K.K. Aravindakshan; Abraham Joseph (Egyptian Journal of Petroleum)
Two N(4)-substituted thiosemicarbazones, anisoin- and furoin N(4)-methyl(phenyl) thiosemicarbazone (AMPTSC and FMPTSC, respectively) have been tested as inhibitors on the corrosion of mild steel in 1 M HCl solution using electrochemical impedance spectroscopy (EIS), potentiodynamic polarization (PDP) methods, adsorption studies and surface morphological studies. Polarization measurements revealed the mixed type inhibitor character. The inhibiting action of these molecules is discussed in terms of blocking the electrode surface by the adsorption of inhibitor molecules obeying Langmuir isotherm. The lowest corrosion rate was obtained with FMPTSC. Surface morphological studies also gave unfailing results.